Brown fat necrosis with calcifications in the newborn: Risk factors, radiographic findings, and clinical course - Golden, Eleza T; Dickson, Paula; Simoneaux, Stephen (Indian Journal of Radiology and Imaging, 2018)
Objective: To describe the radiographic appearance of subclinical calcified brown fat necrosis and the associated clinical and laboratory findings. Materials and Methods: Picture Archiving and Communications Sytem (PACS) was searched using keywords “soft tissue calcification” and “chest.” The clinical record was searched for prior cardiac surgery, bypass, Extracorporeal Membrane Oxygentation (ECMO) and prostaglandin use. Age when calcifications were first detected, location, resolution, and associated laboratory abnormalities were recorded. Results: Nine patients were identified. None had skin lesions. All patients had congenital heart disease and had experienced cardiac/respiratory arrest and/or severe hypotension 1–6 weeks before soft tissue calcifications occurred. Calcifications resolved by 9 weeks to 5 months in 3 patients. The remaining were either deceased or lacked follow-up imaging. Renal ultrasound was performed in all but 1 patient. Nephrocalcinosis was only seen in 1 patient. Conclusion: Brown fat necrosis is subclinical, diagnosed on plain film, and likely self-limited. It occurs in term and preterm infants who have undergone significant systemic stress and carries a poor prognosis.
Keywords: Neonate; neonatal imaging; subcutaneous fat necrosis